Rivelazione Cristiana E Filosofia: La Strada Della Verità : Orientamento e finalità - Palmitessa, Giovanni (Lateranum, 2020)
The article intends to reflect upon a comparison between Christian revelation and philosophy. We are convinced that the question of a comparison between the event of revelation and philosophical speculation is still urgent today, maybe even more than in the past. By stirring up the mind, the Christian revelation stimulates the philosophical reflection to go further, to break new ground, to set out to a more penetrating contact with the truth of man and of Christ. The search for truth, the search for answers concerning the ultimate sense of life as well as of the world is certainly part of philosophical research, but if it is not illuminated by Christian revelation, it will always turn out to be muddled and self-referential, and it will therefore become day by day incapable to turn the eyes upward in daring to reach the truth of Being.